2016
DOI: 10.1038/srep34254
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferases and stress-related genes expression in zebrafish larvae after exposure to heat and copper during reprogramming of DNA methylation

Abstract: DNA methylation, a well-studied epigenetic mark, is important for gene regulation in adulthood and for development. Using genetic and epigenetic approaches, the present study aimed at evaluating the effects of heat stress and copper exposure during zebrafish early embryogenesis when patterns of DNA methylation are being established, a process called reprogramming. Embryos were exposed to 325 μg Cu/L from fertilization (<1 h post fertilization - hpf) to 4 hpf at either 26.5 °C or 34 °C, followed by incubation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 60 publications
4
31
0
1
Order By: Relevance
“…In other vertebrates, little is known about reprogramming. In fish, the only studies so far have been conducted in zebrafish, Danio rerio (Fang, Thornton, Scheffler, & Willett, 2013;Mhanni & McGowan, 2004), and it has been shown that DNA methylation reprogramming represents a highly critical window sensitive to environmental stress (Dorts et al, 2016;Martin, Laforest, Akimenko, & Ekker, 1999). Deciphering TEI, environmental cues and reprogramming are consequently important to understand the putative role of epigenetics in rapid adaptation and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In other vertebrates, little is known about reprogramming. In fish, the only studies so far have been conducted in zebrafish, Danio rerio (Fang, Thornton, Scheffler, & Willett, 2013;Mhanni & McGowan, 2004), and it has been shown that DNA methylation reprogramming represents a highly critical window sensitive to environmental stress (Dorts et al, 2016;Martin, Laforest, Akimenko, & Ekker, 1999). Deciphering TEI, environmental cues and reprogramming are consequently important to understand the putative role of epigenetics in rapid adaptation and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant elevation in total Cu concentrations in the larvae, which suggests that any slight increase in concentrations in water and chorions was not elevated enough for bioaccumulation into embryos and larvae. This is also supported by no significant elevation of metallothionein gene transcription in hatched larvae, a sensitive marker for induction of metal detoxification mechanisms (Dorts et al ). Previous studies on cod embryos and larvae found elevated mortality in larvae exposed to nominal concentrations of 11.5 μg/L Cu (Granmo et al ) and prolonged developmental time and morphological abnormalities including spinal deformations, decreased hatching rate, and reduced larval viability after exposure to nominal Cu concentrations of approximately 10 μg/L (Swedmark and Granmo ).…”
Section: Discussionmentioning
confidence: 92%
“…Dorts et al . () demonstrated the combined effects of metal contamination (copper) and heat stress in zebrafish ( Danio rerio ) embryos during the DNA methylation reprogramming event. The embryos were exposed to CuCl 2 (0 and 325 μg L −1 ) from fertilization to 4 hours post‐fertilization (hpf), at either 26.5°C or 34°C, and then incubated at control conditions (26.5°C) till 96 hpf.…”
Section: Epigenetics In Aquaculturementioning
confidence: 99%
“…Temperature control is crucial in aquaculture, and its variation can have severe consequences for production, as it strongly influences growth, feeding rate and survival of the cultured organisms (Mizanur et al 2014). Dorts et al (2016) demonstrated the combined effects of metal contamination (copper) and heat stress in zebrafish (Danio rerio) embryos during the DNA methylation reprogramming event. The embryos were exposed to CuCl 2 (0 and 325 lg L À1 ) from fertilization to 4 hours post-fertilization (hpf), at either 26.5°C or 34°C, and then incubated at control conditions (26.5°C) till 96 hpf.…”
Section: Epigenetics In Aquaculturementioning
confidence: 99%